Transcriptome Analysis Reveals AI-2 Relevant Genes of Multi-Drug Resistant Klebsiella pneumoniae in Response to Eugenol at Sub-MIC - Wang, Yi-ming; Dong, Wen-long; Odah, Kokou Ayefounin; Kong, Ling-cong; Ma, Hong-xia (Frontiers in Microbiology, 2019)
Eugenol, the major active essential oil component of clove, was reported to possess QS (quorum sensing) inhibitory activity. A previous study found that eugenol could bind to quorum sensing receptors of Pseudomonas aeruginosa and down-regulate the expression of Streptococcus mutans virulence genes at sub-MIC (minimum inhibitory concentration) without affecting the bacterial growth. However, the alterations of QS signal molecules at transcription levels was not well understood. To better understand interactions of Klebsiella pneumoniae in response to eugenol and explore molecular regulations, transcriptome sequencing was performed. A total of 5779 differentially expressed genes (DEGs) enriched in a variety of biological processes and pathways were identified. The transcriptional data was validated by qPCR and the results showed that the expression profiles of 4 major genes involved in autoinducers-2 (AI-2) synthesis, including luxS, pfs, and lsrK were consistent with transcriptome analysis except for lsrR, a transcriptional repressor gene of lsr operon, which may repress the expression of following genes responsible for AI-2 signal transmission in vivo. In vitro AI-2 synthesis assay also revealed that eugenol could inhibit AI-2 generation. The results of our study offer insights into the mechanisms of QS inhibitory activity and K. pneumoniae AI-2 alterations after eugenol treatment.